PENGUKURAN INDEKS GLIKEMIK DAN BEBAN GLIKEMIK SUSU NABATI BERBAHAN DASAR BIJI JALI DENGAN SUBTITUSI SARI BUAH NAGA MERAH - Regita Sri Jayanti (2022)
The prevalence of diabetes mellitus in 2018 increased by 1.6% compared to 2018. The impact of diabetes mellitus can be prevented by consuming foods that have a glycemic index value and low glycemic load such as vegetable milk made from jali seeds with substitution of red dragon fruit juice. Consumption of foods with low GI can affect the decrease in blood glucose slowly. The purpose of this study was to determine the value of the glycemic index and glycemic load of vegetable milk made from jali seeds with the substitution of red dragon fruit juice. This study used an experimental study design with 11 healthy adult subjects. There were two groups: the control group was only given pure glucose and the treatment group was given jali seed vegetable milk with the substitution of red dragon fruit juice containing 50 g of carbohydrates. The results of the intervention showed that the average blood glucose response of the treatment group was lower than the control group. The results of the paired t-test showed that the AUC area of the treatment group was significantly different (p<0.005) compared to the control group. The GI value of plant-based milk made from jali seeds with substitution of red dragon fruit juice is 37.35, including the low category, while the BG value of 4.81 is in the low category. Consumption of foods with low GI and BG does not make blood glucose spike significantly, it is beneficial for people with diabetes mellitus in controlling blood glucose.